2013
DOI: 10.1111/bju.12491
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and non‐muscle‐invasive bladder cancer: not just a coincidence?

Abstract: [2] shows a high NPV only when the threshold was set at the low level of 2 for each parameter. Predictably, at this threshold the PPV was extremely low, and therefore many men would still undergo unnecessary biopsy. Another similar paper advocated a mean threshold of 3, but even then the PPV was 38% with a NPV of 95% [3]. Both these papers are retrospective studies, in particular the MRI readings were done retrospectively. Nevertheless, the low PPV is disappointing. The results of prospective studies with mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…involved, as chronic hyperinsulinemia or hyperglycemia has been shown to promote tumor cell proliferation and metastasis (44)(45)(46)(47). Similarly, elevated levels of insulin-like growth factor (IGF)-1 induces cellular proliferation while inhibiting apoptosis (44)(45)(46)(47). Excess adiposity also creates a pro-inflammatory environment, and this may contribute to poorer prognostic outcomes in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…involved, as chronic hyperinsulinemia or hyperglycemia has been shown to promote tumor cell proliferation and metastasis (44)(45)(46)(47). Similarly, elevated levels of insulin-like growth factor (IGF)-1 induces cellular proliferation while inhibiting apoptosis (44)(45)(46)(47). Excess adiposity also creates a pro-inflammatory environment, and this may contribute to poorer prognostic outcomes in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanisms responsible for this association are unclear . Postulated mechanisms include the effects of hyperinsulinemia, hyperglycemia and signal pathways of insulin‐like growth factor receptors . Regardless of an unknown mechanism, several large‐scale epidemiology studies showed a significant association between DM and UBC.…”
Section: Discussionmentioning
confidence: 99%
“…There has been extensive work to try to identify a link between bladder cancer and type 2 diabetes, with some studies suggesting an increased riskhowever, again, potential confounders exist, as the diabetic population is more likely to have regular urine testing, which may account for a higher incidence of bladder cancer. 35 DIABETES AND METABOLIC SYNDROME 31 TESTICULAR CANCER Testicular cancer patients have an increased risk for CVD, which might be related to the increased prevalence of the metabolic syndrome in this group of patients. 36 A recent study assessed the prevalence of metabolic syndrome and the 10-year CVD risk in a cohort of 255 testicular germ cell tumour survivors (median age, 38.7 years; interquartile range, 31-48) at a mean of 7.8 years after anticancer treatment, and compared these with data obtained from 360 healthy men.…”
Section: Bladder Cancermentioning
confidence: 99%